1988
DOI: 10.1128/jb.170.3.1297-1304.1988
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional regulation, nucleotide sequence, and localization of the promoter of the catBC operon in Pseudomonas putida

Abstract: The catB and catC genes encode cis,cis-muconate lactonizing enzyme I (EC 5.5.1.1) and muconolactone isomerase (EC 5.3.3.4), respectively. These enzymes are required for the dissimilation of benzoate to 13-ketoadipate by Pseudomonas putida and are under coordinate transcriptional regulation. By deletion analysis and the use of pKT240 as a promoter probe vector, we located a single promoter region for the catBC operon upstream of catB. RNA-DNA hybridization studies, together with reverse transcriptase mapping, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 36 publications
(26 reference statements)
0
29
0
Order By: Relevance
“…4-n4- (2,26). By using unidirectional deletion mutants, it was shown that the gene coding for 23DBDO with only 58 bp upstream from the initiation codon ATG was expressed in P. putida (data not shown), suggesting that the promoterlike sequence located between other in nucleotide sequence.…”
Section: P Pmentioning
confidence: 99%
“…4-n4- (2,26). By using unidirectional deletion mutants, it was shown that the gene coding for 23DBDO with only 58 bp upstream from the initiation codon ATG was expressed in P. putida (data not shown), suggesting that the promoterlike sequence located between other in nucleotide sequence.…”
Section: P Pmentioning
confidence: 99%
“…Divergence of the cat regions within P. putida from the corresponding genes in Pseudomonas strain RB1 was indicated by the finding that cat genes from the latter organism were stably maintained on broad-host-range plasmids after their introduction into mutants derived from the P. putida biotype strain (1,2). To ascertain the extent to which cat genes from the P. putida biotype strain and from the Pseudomonas strain RB1 differ in nucleotide sequence, it was necessary to clone the cat region from the biotype strain.…”
mentioning
confidence: 99%
“…For catechol catabolism, sequencing of the corresponding cat genes from several gram-negative strains has shown that isofunctional genes in these bacteria are clearly homologous (1,10,26,32,43,44,55). Similarly, the catechol 1,2-dioxygenase of Arthrobacter sp.…”
mentioning
confidence: 99%